PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SEKOLAH DASAR - Azizah Azizah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
The background of this study is the low absorption of learners, especially in grade V SDN 019 Bumi Ayu studyresult of low student science. This can be seen from the students score in the middle of the average value of only61.5. The percentage of students who reach the KKM is only 50% out of 20 students, and the total number ofcompleted students is only 10 people. This research is a classroom action research conducted on Grade Vstudent of SDN 019 Bumi Ayu. The results obtained data Activity teachers reached 41%. At the second meetingalso reached 54%. Meanwhile, after the second cycle increased at the third meeting with a percentage of 66%.At the fourth meeting with a percentage of 75%. While the activity of students on the first cycle of the firstmeeting with a percentage of 41% At the second meeting with a percentage of 58% in the second cycle of studentactivity with a percentage of 70%. The 4th meeting was a percentage of 79%. The result of science learning ofgrade V students on the basic score is 50% of the total students, whereas in daily test I students reach KKM to60% of the total students, and in daily test II the number of students reaching KKM increased to 80%. Similarly,in the initial data the average value of 61.5 cycles I increased with the average student score 67 and cycle IIwith the average score of 72.25 students.